2008
DOI: 10.2166/nh.2008.041
|View full text |Cite
|
Sign up to set email alerts
|

Detection of permanent open water surfaces in central Siberia with ENVISAT ASAR wide swath data with special emphasis on the estimation of methane fluxes from tundra wetlands

Abstract: Permanent water bodies not oniy store dissolved CO2 but are essential for the maintenance of wetlands in their proximity. From the viewpoint of greenhouse gas (GHG) accounting wetland functions comprise sequestration of carbon under anaerobic conditions and methane release. The investigated area in central Siberia covers boreal and sub-arctic environments. Small inundated basins are abundant on the sub-arctic Taymir lowlands but also in parts of severe boreal climate v^fhere permafrost ice content is high and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 9 publications
0
36
0
Order By: Relevance
“…Although these four approaches were designed according to different requirements, their performances were satisfactory over the studied areas (17 out of 20 water masks reaching an overall accuracy larger than 90%). Other studies using SAR data for water monitoring locally and regionally under different environments can be listed, such as [10][11][12]. Mapping water bodies at global scale using SAR data was limited due to the lack of global observations, and the fact that SAR data are not easy to access freely.…”
Section: Introductionmentioning
confidence: 99%
“…Although these four approaches were designed according to different requirements, their performances were satisfactory over the studied areas (17 out of 20 water masks reaching an overall accuracy larger than 90%). Other studies using SAR data for water monitoring locally and regionally under different environments can be listed, such as [10][11][12]. Mapping water bodies at global scale using SAR data was limited due to the lack of global observations, and the fact that SAR data are not easy to access freely.…”
Section: Introductionmentioning
confidence: 99%
“…For soil moisture retrieval the signal is impacted if the area covered by open water surface within the footprint is large [38]. A surface water fraction flag, derived from the Global Lakes and Wetlands Database [55], exists but it does not take wetland dynamics, temporary inundation and small lakes into account [54]. An improved flag of this kind could be derived from ASAR data [13,56].…”
Section: Discussionmentioning
confidence: 99%
“…The persistence of lake ice on large lakes well into the summer and the associated water body classification issues have already been pointed out by [47]. To identify any water surface effects, the water areas identified by the classification were replaced by the value −20 dB, which is a typical C-band backscatter value for smooth water surfaces in the used dataset [47,54]. This builds the reference dataset.…”
Section: Methodsmentioning
confidence: 99%
“…Wetland complexes agree in most parts with the classification of this study (compare Figure 14: "forested shrubs-and moss-dominated mires" agree with "areas with high degree of saturation", "sphagnum dominated bogs with pools and open stand trees" agree with regions with a mixture of "water bodies" and "areas with high degree of saturation".) Bartsch et al [10] suggested the use of metrics such as water bodies density for tundra wetland complex retrieval. A combined use of those two classes may lead to the delineation of classes as used in [35].…”
Section: Assessment and Discussionmentioning
confidence: 99%
“…The ENVISAT ASAR instrument operating in Wide Swath mode provides C-band backscatter data with a spatial resolution of 150 m. Thus, small tundra ponds and wetland patches can be captured, which are smaller than the resolution of coarse to medium resolution satellite data (about 25 km to 500 m). Open water bodies can be mapped efficiently and accurately using ENVISAT ASAR WS data as described in [10]. In continuation of that study, the approach has shown high applicability to derive the inundation dynamics of the boreal and tundra environments [11].…”
Section: Introductionmentioning
confidence: 95%